A comparison of injuries in elite male and female football players: A five‐season prospective study. (27th March 2017) - Larruskain, J.; Lekue, J. A.; Diaz, N.; Odriozola, A.; Gil, S. M.
Abstract : The aim was to compare the epidemiology of injuries between elite male and female football players from the same club. Injuries and individual exposure time in a male team and a female team, both playing in the Spanish first division, were prospectively recorded by the club's medical staff for five seasons (2010‐2015) following the FIFA consensus statement. Total, training, and match exposure hours per player‐season were 20% higher for men compared to women ( P< .01). Total, training, and match injury incidence were 30%‐40% higher in men ( P≤ .04) mainly due to a 4.82 (95% confidence interval [CI] 2.30‐10.08) times higher incidence of contusions, as there were no differences in the incidence of muscle and joint/ligament injuries ( P≥ .44). The total number of absence days was 21% larger in women owing to a 5.36 (95% CI 1.11‐25.79) times higher incidence of severe knee and ankle ligament injuries. Hamstring strains and pubalgia cases were 1.93 (95% CI 1.16‐3.20) and 11.10 (95% CI 1.48‐83.44) times more frequent in men, respectively; whereas quadriceps strains, anterior cruciate ligament ruptures, and ankle syndesmosis injuries were 2.25 (95% CI 1.22‐4.17), 4.59 (95% CI 0.93‐22.76), and 5.36 (95% CI 1.11‐25.79) times more common in women, respectively. In conclusion, prevention strategies should be tailored to the needs of male and female football players, with men more predisposed to hamstring strains and hip/groin injuries, and women to quadriceps strains and severe knee and ankle ligament injuries.